1998
DOI: 10.1016/s0969-806x(98)00141-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyethylene based graft copolymers. Applications in the immobilization of enzymes

Abstract: In the last few years new copolymeric supports for the immobilization of biological compounds have been developed. The graft copolymer polyethylene-g.co-hydroxyethyl methacrylate, partially hydrolyzed, has shown to be a very promising support for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 2 publications
1
13
0
1
Order By: Relevance
“…Particles of LDPE (2 g) with a granularity of 500 lm were dispersed in 30 cm 3 of HEMA solutions in MeOH. The mixtures were then gamma irradiated at a 60 Co source at dose-rates of 0.3 and 0.5 kGy h À1 .…”
Section: Radiation Graft Copolymerisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Particles of LDPE (2 g) with a granularity of 500 lm were dispersed in 30 cm 3 of HEMA solutions in MeOH. The mixtures were then gamma irradiated at a 60 Co source at dose-rates of 0.3 and 0.5 kGy h À1 .…”
Section: Radiation Graft Copolymerisationmentioning
confidence: 99%
“…The use of 2-hydroxyethyl methacrylate (HEMA) as a grafting monomer onto a range of polymeric substrates with the aim of producing new biomaterials has been increasingly successful. Previous studies showed that the presence of HEMA in copolymers improves the biocompatibility of the materials [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, scientists have keen to choose polymeric support as an efficient one for immobilizing lipases. Few reports are available in the literature where lipases were bound to the polymeric microspheres/particles [17][18][19][20]. In this study, the immobilization of lipases is done at the time of phase inversion of polymer from organic medium.…”
Section: Introductionmentioning
confidence: 99%
“…While ultrasonic grafting is still a very new research area, irradiation technology was first used in polymer chemistry by Charlesby (15) in 1952. He found that irradiation can be used to synthesize cross-linked polyolefin materials, and subsequently more research appeared on monomer grafting by irradiation to the PEW (16,17). Irradiation is also an effective and relatively new method to initiate chemical grafting reactions.…”
Section: Introductionmentioning
confidence: 99%